Community diagnosis by conducting family health survey in the field practice area of a medical college - Patel, Mizba Basheer; Maheen, Moniza; Shaikh, Fawwad M.; Chandrasekhar, A. (International Journal Of Community Medicine And Public Health, 2019)
Background: In a developing country like India, with limited resources health needs of individuals and community are enormously increasing. Health related problems may be addressed amicably by community diagnosis. Assessment and prioritization of health issues followed by formulation of action plans with strategies and their implementation can be effectively achieved, by using family health surveys. Methods: Using family health survey 500 families, constituting 2640 individuals were studied. Their health status and socio-demographic details were taken. Households and families were selected randomly. Data entry and analysis was done by appropriate use of statistical tools. Results: Study showed 52.27% males and 47.73% females. Majority (51.5%) belonged to 16-45 years followed by 6-15 years of age (25%). Among 9.09% of the under-five, fully immunized were 90.4% and partially immunized were 9.6%. 6.06% were above 60 years. Nuclear families were 68%. Majority (36%) of the families belonged to socio-economic class II (modified B.G. Prasad classification). 10.6% were illiterate and 11.3% were below seven years of age. Overcrowding was present in 24% of the families. Common morbidities were hypertension (32.2%), diabetes (26.9%), respiratory diseases (19.2%) eye problems (6.2%) and skin diseases (3.8%). Geriatric problems were present in one out of four individuals. Conclusions: Family health survey can be used as an educational tool for undergraduate medical students to understand common morbidities and determinants of diseases in the community. Family health surveys are important for a community as necessary intervention can be done for illnesses and health-related problems.